A randomized two-way crossover bioequivalence study in healthy adult volunteers of paediatric zidovudine/lamivudine/nevirapine fast-disintegrating fixed-dose combination tablet. (18th November 2016) - Joshi, Anjali; Gbadero, Daniel; Esseku, Fredrick; Adesanya, Olufikayo J; Adeyeye, Moji C
Abstract: Objective: The bioequivalence study was conducted to compare the developed paediatric fixed-dose combination (FDC) zidovudine/lamivudine/nevirapine (60/30/50 mg) tablet – the test formulation – with the combined mixture of single-entity innovator products (reference product). Methods: A single-dose open-label randomized two-way crossover study was conducted in healthy adult African volunteers after an informed consent was obtained. The 24 volunteers, divided into two groups, were administered the products after an overnight fast on two treatment days with 14 days of washout period. Blood samples were collected for 96 h and analysed using a validated RP-HPLC-UV assay method. Pharmacokinetic (PK) parameters (non-compartmental model) were assessed with WinNonlin® software. Analysis of variance (ANOVA) and FDA bioequivalence statistical criterion of 90% CI or 80% to 125% range (set at P < 0.05) of least square geometric means (LSGM) ratios of test: reference product for C max, AUC0– t, and AUC0–∞ were determined. Results: ANOVA indicated that the period, sequence and formulation had no significant effect on the PK parameters ( P > 0.05). The 90% CIs for all the drugs were within the 80% to 125% range. Conclusion: The developed FDC tablet is bioequivalent to the reference product.